Multicenter, Randomized, Double‐Blind Study Protocol Using Human Spinal Cord Recording Comparing Safety, Efficacy, and Neurophysiological Responses Between Patients Being Treated With Evoked Compound Action Potential–Controlled Closed‐Loop Spinal Cord Stimulation or Open‐Loop Spinal Cord Stimulation (the Evoke Study). Issue 3 (3rd March 2019) - Levy, Robert; Deer, Timothy R.; Poree, Lawrence; Rosen, Steven M.; Kapural, Leonardo; Amirdelfan, Kasra; Soliday, Nicole; Leitner, Angela; Mekhail, Nagy
Abstract : Background: The spinal cord (SC) response to stimulation has yet to be studied in a pivotal clinical study. We report the study design of an ongoing multicenter, randomized, double‐blind, controlled, parallel‐arm study of an evoked compound action potential (ECAP) controlled closed‐loop spinal cord stimulation (SCS) system, which aims to gain U.S. Food and Drug Administration approval. Methods: This study will enroll 134 SCS candidates with chronic trunk and limb pain from up to 20 United States sites. Subjects are randomized 1:1 to receive ECAP‐controlled closed‐loop or open‐loop, conventional SCS. The primary objective is noninferiority of closed‐loop stimulation determined by the proportion of subjects with ≥50% reduction in overall trunk and limb pain and no increase in pain medications at the three‐month visit. If noninferiority is met, superiority is tested. In addition, measures recommended by IMMPACT (e.g., pain intensity, functional disability, emotional functioning, quality of life, impression of change, and sleep), neurophysiological properties (e.g., SC activation, conduction velocity, chronaxie, and rheobase), and safety are analyzed. Discussion: All approved SCS therapies, regardless of the presence or absence of stimulation induced paresthesias, produce fixed‐output stimuli; that is, the energy delivered from the electrode array has a defined output irrespective of the neural response of SC fibers. An SCS system has been developed that directly measures the neurophysiologic activation of the SC to stimulation (i.e., ECAP amplitude) and uses this information in a feedback mechanism to produce closed‐loop SCS to maintain optimal and stable activation of the SC. This study represents the first randomized, double‐blind, pivotal study in the field of neuromodulation to measure SC activation in ECAP‐controlled closed‐loop versus open‐loop stimulation and is expected to yield important information regarding differences in safety, efficacy, and neurophysiological properties. The potential clinical utility of these objective measurements of SC activation and other neurophysiological properties promises to improve outcomes of SCS for chronic pain patients.